Hannah Arendt and Politics - Robaszkiewicz, Maria Anna; Weinman, Michael D.

Du Châtelet et la tradition critique de la Bible. De la ‘philofolie’ aux Examens - Hagengruber, Ruth Edith (La Lettre clandestine n° 30: Émilie Du Châtelet et la littérature clandestine. Moreau, P.F. & Seguin, M.S. (Eds.). Paris)

Die „dritte Wissensdimension“. Eine Epistemologie für eine neue Wissenswelt - Hagengruber, Ruth Edith (Sitzungsberichte der Leibniz-Sozietät der Wissenschaften 150/151, Jahrgang 2022: „Cyberscience – Wissenschaftsforschung und Informatik. Digitale Medien und die Zukunft der Kultur wissenschaftlicher Tätigkeit. Arbeitskreis „Emergente Systeme/Informatik und Gesellschaft“ der Leibniz-Sozietät der Wissenschaften zu Berlin in Kooperation mit der Gesellschaft für Wissenschaftsforschung“)

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne)
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz

Époque Émilienne
Keywords: Émilie Du Châtelet; History of Science; Kant; Newton; Maupertuis; Voltaire

“Mehr wert als tausend Männer” – Luise Adelgunde Victorie Kulmus Gottsched und die wahre Minerva - Hagengruber, Ruth (Musikwissenschaft der Vielfalt. Festschrift für Rebecca Grotjahn zum 60. Geburtstag)

Out of the Box – into the Green and the Blue - Hagengruber, Ruth (Philosophisches Jahrbuch 128. Jahrgang I/2021)

Philosophinnen an die Macht - Hagengruber, Ruth (Female Recruiting Report (3))

Ökonomie, Technik, Umwelt: Die Zukunft bestimmen, während wir die Vergangenheit überdenken: Defining the Future – Rethinking the Past - Hagengruber, Ruth (Konsens)

Vizepräsidentin a.D. des DAB, Prof. Dr. Ulrike Detmers verleiht zum 20. Mal den von ihr ins Leben gerufenen Preis‚ Managerin des Jahres - Hagengruber, Ruth (Konsens)

Der Elisabeth-von-Böhmen-Preis zur Erforschung der Geschichte der Philosophinnen wird zum dritten Mal verliehen - Hagengruber, Ruth (Konsens)

Frauen aus aller Frauen Länder gestalten die Zukunft Deutschlands. Jahrestagung des DAB am 30. April 2021 - Hagengruber, Ruth (Konsens)

Women Philosophers from the Renaissance to the Enlightenment
This collection of essays presents new work on women’s contribution to philosophy between the Renaissance and the mid-eighteenth century. They bring a new perspective to the history of philosophy, by highlighting women’s contributions to philosophy and testifying to the rich history of women’s thought in this period. By showing that women were active in many branches of philosophy (metaphysics, science, political philosophy cosmology, ontology, epistemology) the book testifies to the rich history of women’s thought across Europe in this period. The scope of the collection is international, both in terms of the philosophers represented and the contributors themselves from Britain and North America, but also from continental Europe and from as far afield as Australia and Brazil. The philosophers discussed here include both figures who have recently come to be better known (Elisabeth of Bohemia, Anne Conway, Mary Astell, Catharine Trotter Cockburn, Emilie du Châtelet), and less familiar figures (Moderata Fonte, Lucrezia Marinella Arcangela Tarabotti, Tullia d’Aragona, Madame Deshoulières, Madame de Sablé, Angélique de Saint-Jean Arnauld d’Andilly, Olivia Sabuco, Susanna Newcome). The chapters in this book were originally published as a special issue of the British Journal for the History of Philosophy.
Keywords: History of Women Philosophers; Methodology; History of Philosophy; Women's Studies; Gender History

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)

Der Deutsche Akademikerinnenbund ist Mitglied der Europäischen Bewegung Deutschland (EBD) - Hagengruber, Ruth Edith (Konsens (2021), 9)

Center for the History of Women Philosophers and Scientists Documentation 2016-2019 (Version 1)

The Paris Ms Fr. 12265. A Critical and Historical Online Edition. https://historyofwomenphilosophers.org/dcpm/ (2021-2022)

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)
Of the many outstanding female philosophers of the European Enlightenment, Emilie Du Châtelet excelled as a physicist, a philosopher, and a mathematician, as well as a Bible critic. She was famous in her lifetime and was not completely forgotten thereafter. Among her admirers, correspondents and friends were the most acknowledged scholars of her time, including Voltaire, Clairault, Maupertuis, Diderot, Helvetius, La Mettrie, Buffon, Christian Wolff, Leonard Euler, and Johann II Bernoulli. Her philosophical work enjoyed high reputation and her opus magnum, the Institutions physiques, was translated into Italian and German and proved her to be an intellectual of European stature. Its defense of living forces and its implied forecast into dynamics as well as her methodological grounding of scientific knowledge as hypothetical, impacted philosophy and science. Reality must by nature escape us. What we perceive are phenomena. Du Châtelet explains the function of space and time to trace us back to the origin of phenomena. Her influence on Kant is evident. Next to her writings in physics, mathematics, philosophy, language, and logic, she contributed to morality and ethics. Du Châtelet left an opus of quite systematic breadth. This impressive publishing activity excels in the amount of its scientific and philosophical production to which a vast collection of manuscripts must be added.She argued against prejudice and idolatry in philosophy and science. Science is a cooperative undertaking over history and beyond nations. Her moral writings align with ideas of the French materialists. Du Châtelet translated and commented on Newton’s Principia, preparing thus the fertile soil of the generation of physicists to come in France.
Keywords: aura Bassi Luise Gottsched Immanuel Kant Dourtous de Mairan Johann II Bernoulli Algarotti Buffon d’Alembert La Mettrie Principle of contradiction Hypotheses Enlightenment Leibniz-Clarke Correspondence Living forces Dead forces; happiness Space Imaginary beings Monads Epicurus Ethics Women philosophers Newton’s laws Principia Motion inertia Active force Vis viva Vis mortua Hypothetic reasoning Hypotheses; a priori principles; Experience; Dead forces; Living forces; Energy Dynamics

Women in Early Modern Philosophy and Science: An Introduction - Hagengruber, Ruth Edith (Encyclopedia of Early Modern Philosophy and the Sciences)
Essential ideas significantly connected to humanism, Renaissance, and early modern philosophy stem from women’s pens. The supportive role of women in the early modern period has hardly been recognized up to today. The relevant issues women have contributed to range from commentaries on and critiques of the Bible, and their demands for equality and the critique of political institutions, topics that became eminent enhancers of political and societal change in the relevant period of early modern philosophy, to enlightenment philosophy.

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

The Stolen History—Retrieving the History of Women Philosophers and its Methodical Implications - Hagengruber, Ruth (Methodological Reflections on Women’s Contribution and Influence in the History of Philosophy. Women in the History of Philosophy and Sciences, Vol 3)

Pressure on Enlightenment. Bible Critics from Nogarola to Du Châtelet - Hagengruber, Ruth (Dianoia 31, no. XXV)
The Enlightenment is well known for its critical analysis of the Bible. Though the Renaissance sources have been acknowledged as an inspiration of this movement, the Querelle des Femmes and its critique of the Bible has never been considered as a possible catalyst for the enlightened philosophical discourse. For centuries women have fought against interpretations of the Bible.This paper argues that the Querelle des Femmes criticized the Bible not only because of its patriarchal content but also criticized philosophical thinking that, for supporting the views from the Bible and its misogynist stance, misusing the instruments of rational philosophy. Arguments from 1400-1750, from Nogarola to Du Châtelet proof women philosophers’ fight in favour of a critique of the bible from a rational point of view, reflecting also on the status of what it meant, to argue rationally.
Keywords: Keywords: Bible critics; Isotta Nogarola; Querelle des femmes; Enlightenment; Émilie Du Châtelet.

Der männliche Gott. Bibel- und Gesellschaftskritik in der Tradition der Philosophinnen der frühen Neuzeit - Hagengruber, Ruth (Männlich, weiblich, divers? Philosophische Anthropologie der Geschlechter)

Methodological Reflections on Women’s Contribution and Influence in the History of Philosophy. Women in the History of Philosophy and Sciences, Vol 3

The Saint Petersburg Manuscripts. A historical and critical online edition. https://historyofwomenphilosophers.org/stp/ (2020-2021)

Die gestohlene Geschichte - Hagengruber, Ruth (philosophie Magazin)
Die Philosophiegeschichte, die heute gelehrt wird präsentiert sich als ein Kanon, der von "großen Männern" dominiert wird. Doch das ist nicht richtig und vor allem, es war nicht immer so. Es gab großartige und einflussreiche Denkerinnen, von Hildegard von Bingen bis Hannah Arendt und Edith Stein, "in allen Ländern und zu allen Zeiten", wie der aufgeklärte Historiograph Jakob Brucker 1745 in seiner Philosophiegeschichte schrieb.
Keywords: women philosophers; stolen history; Ruth Hagengruber

Frauen aus der Mitte Deutschlands - Hagengruber, Ruth Edith (Konsens)
Keywords: Interview; Europe; Women; Diversity

Women Philosophers in Early Modern Philosophy - Hagengruber, Ruth Edith (British Journal for the History of Philosophy. Vol. 27)

Émilie Du Châtelet zwischen Leibniz und Kant. Du Châtelet in der Eberhard-Kant-Kontroverse - Hagengruber, Ruth Edith (Emilie Du Châtelet und die deutsche Aufklärung)
In seiner Auseinandersetzung mit Immanuel Kant bestreitet Johann August Eberhard Kants Anspruch, in seiner Transzendentalphilosophie die Reichweite und Grenzen des Verstandes auf neue, zuvor nicht dagewesene Weise definiert zu haben. Eberhard dagegen meint die Prinzipien und Grundbegriffe transzendentalphilosophischer Erkenntniskritik schon aus der Leibniz-Wolffschen Schule ableiten zu können. An einschlägiger Stelle -- im dritten Teil seiner Ausführungen Über den wesentlichen Unterschied der Erkenntnis durch die Sinne und durch den Verstand -- belegt er diese Behauptung mit einem Verweis auf die {\glqq}Definition{\grqq} der Erscheinung in den Institutions physiques der Philosophin und Mathematikerin Du Châtelet.

Introduction - Hagengruber, Ruth Edith; Hutton, Sarah (British Journal for the History of Philosophy)

Emilie Du Châtelet und die deutsche Aufklärung. Vol. 3. Philosophie History of Science Frauen in Philosophie und Wissenschaft. Women Philosophers and Scientists

Emilie Du Châtelet und ihre Wirkung in Deutschland - Hagengruber, Ruth Edith; Hecht, Hartmut (Emilie du Châtelet und die deutsche Aufklärung)

Emilie Du Châtelet und die deutsche Aufklärung
In diesem Band werden neueste Forschungen zur Physikerin, Mathematikerin und Philosophin Emilie Du Châtelet (1706-1749) vorgestellt. Emilie Du Châtelet genoss in der deutschen Aufklärung eine hohe Reputation. Sie verband Leibniz Metaphysik mit der Physik von Newton und gelangte zu erstaunlichen Ergebnissen, die die Physik auf den Weg zu Einsteins Energieformel führte. Ihre Werke wurden sofort ins Deutsche übersetzt, Kant nimmt in seiner ersten Dissertation von 1747 auf sie Bezug. Die Sammlung stellt Texte vor, die den Einfluss der deutschen Aufklärung auf Du Châtelets und Du Châtelets Einfluss auf die deutsche Philosophie diskutieren. Die großen Namen der Epoche stehen hier zur Debatte, Leibniz, Wolff, Boskovic, Euler, Friedrich II, Voltaire, La Mettrie und viele weitere Größen der Aufklärung werden in ihrem Zusammenhang mit Du Châtelet vorgestellt.
Keywords: Emilie Du Châtelet; Immanuel Kant; Leibniz; Aufklärung; Christian Wolff; Luise Gottsched

Relocating Women in the History of Philosophy and Science. Emilie Du Châtelet (1706-1749), Laura Bassi (1711-1778), and Luise Gottsched (1713-1762) in Brucker’s Pinacotheca - Hagengruber, Ruth (Bruniana & Campanelliana)
Abstract · Émilie Du Châtelet (1706-1749), Laura Bassi (1711-1778), and Luise Gottsched (1713-1762) were three philosophers and scientists of outstanding im-portance in their epoch. However, the attribution of importance and reputation to women’s intellectual achievements in this period is a case of its own. This paper investigates the methodical attempt of 18th century historiography, presenting the example of Jakob Brucker and his Pinacoteca to relocate intellectual women in his history of philosophy and science. The relative integration of women into the 18th century intellectual sphere is the starting point of this methodical investigation to retrace its ‘why and how’. Keywords : Emilie Du Châtelet, Luise Gottsched, Laura Bassi, History, Philoso-phy, Science.
Keywords: Keywords : Emilie Du Châtelet; Luise Gottsched; Laura Bassi; History; Philosophy; Science.

Zur Ehrenpromotion von Maria von Welser an der Fakultät für Kulturwissenschaften der Universität Paderborn - Hagengruber, Ruth (Konsens)
Keywords: Maria von Welser; Women; Media; War; Women in War; Refugees

Introduction - Hagengruber, Ruth; Hutton, Sarah (British Journal for the History of Philosophy)

Good Philosophy for a Good Life! How Marie de Gournay (1565-1645) and Emilie du Châtelet (1706-1749) Criticized the Canon and Argued for Women’s Concern - Hagengruber, Ruth Edith (Proceedings of the XXIII World Congress of Philosophy Vol. 29)

Ein selbstloser Akt? Philosophische Gedanken über das Helfen - Hagengruber, Ruth (CARE affair, no. 11)

Brigitte Rauschenbach: Der Geist der Geschlechter - Hagengruber, Ruth (Zeitschrift für philosophische Forschung)

Women Phenomenologists on Social Ontology. Vol. 1. Women in the History of Philosophy and Sciences
Part 1: Social Ontology in Edith Stein and Gerda Walther -- Chapter 1. The Role of Empathy in Experiencing Community (Antonio Calcagno) -- Chapter 2. Meaning of Individuals within Communities: Gerda Walther and Edith Stein on the Constitution of Social Communities (Julia Mühl) -- Chapter 3. Edith Stein on Social Ontology and the Constitution of Individual Moral Identity (William Tullius) -- Chapter 4. The Ontic-Ontological Aspects of Social Life. Edith Stein's Approach to the Problem (Anna Jani) -- Chapter 5. Starting from Husserl: Communal Life according to Edith Stein (Alice Togni) -- Chapter 6. The role of the intellectual in the social organism. Edith Stein's analyses between social ontology and philosophical anthropology (Martina Galvani) -- Chapter 7. The Phenomenology of Shared Emotions - Reassessing Gerda Walther (Thomas Szanto) -- Chapter 8. We-Experience - with Walther (Hans-Bernhard Schmid) -- Chapter 9. Gerda Walther between the phenomenology of mystics and the ontology of communities (Anna Piazza:) -- Chapter 10. Do We-Experiences Require an Intentional Object? On the Nature of Reflective Communities (Following Gerda Walther) (Sebastian Luft) -- Part2: The Ontology of Hedwig Conrad-Martius -- Chapter 11. Essence, Abyss, and Self - Hedwig Conrad-Martius on the Non-Spatial Dimensions of Being (Ronny Miron) -- Chapter 12. ``The reinstatement of the phenomenon''. Hedwig Conrad Martius and the meaning of ``being'' (Manuela Massa) -- Chapter 13. From Collectives to Groups - Sartre and Stein on Joint Action and Emotional Sharing (Gerhard Thonhauser) -- Chapter 14. Women as zoa politika, or: Why There Could Never Be a Women's Party. An Arendtian-Inspired Phenomenology of a Female Political Subject (Maria Robaszkiewicz) -- Chapter 15. Ontology is social. How Arendt Solves a Wittgensteinian Problem (Anna-Magdalena Schaupp) This edited volume examines women's voices in phenomenology, many of which had a formative impact on the movement but have be kept relatively silent for many years. It features papers that truly extend the canonical scope of phenomenological research. Readers will discover the rich philosophical output of such scholars as Edith Stein, Hedwig Conrad-Martius, and Gerda Walther. They will also come to see how the phenomenological movement allowed its female proponents to achieve a position in the academic world few women could enjoy at the time. The book explores the intersection of social ontology, phenomenology, and women scholars in phenomenology. The papers offer a fresh look at such topics as the nature of communities, shared values, feelings, and other mental content. In addition, coverage examines the contributions of Jewish women to the science, who were present at the beginning of the phenomenological movement. This remarkable anthology also features a paper on Gerda Walther written by Linda Lopez McAlister, former editor of the feminist journal Hypatia, who had met Walther in 1976. This book features work from the conference ``Women Phenomenologists on Social Ontology,'' held at the University of Paderborn. Overall, it collects profiles and analysis that unveil a hidden history of phenomenology
Keywords: Europe; Central-History; Ontology; Phenomenology; Philosophy; Political science; Political science / Philosophy

Women Phenomenologists on Social Ontology

"If I Were King!" Morals and Physics in Emilie Du Châtelet’s Subtle Thoughts on Liberty - Hagengruber, Ruth Edith (Women and Liberty)

Creative Algorithms and the Construction of Meaning - Hagengruber, Ruth (Berechenbarkeit der Welt?)

Bergès, Sandrine; Coffee, Alan (Eds.). The Social and Political Philosophy of Mary Wollstonecraft. Oxford University Press, 2017. - Hagengruber, Ruth Edith

Ecofeminist Standpoint of Economic Growth - Hagengruber, Ruth Edith; Karpenko, Kateryna (Gender. Ecologia)

Ecofeminist Standpoint of Economic Growth - Hagengruber, Ruth; Karpenko, Kataryna (Gender. Ecologia.)

Philosophinnen in der Schule - Hagengruber, Ruth (Ethik/Philosophie Didaktik. Praxishandbuch für die Sekundarstufe I und II)

The Long-Lasting Tradition of Women Philosophers as an Insight into the History of Ideas - Hagengruber, Ruth Edith (Materials of the Inter-University Scientific Conference with International Participation)

Soziale Organisation und enzyklopädisches Interesse. Campanellas metaphysische Grundlegung der Sonnenstadt - Hagengruber, Ruth Edith (Politische Utopien der Neuzeit. Thomas Morus, Tommaso Campanella, Francis Bacon)

Emilie du Châtelet, 1706–1749. Transformer of Metaphysics and Scientist - Hagengruber, Ruth Edith (The Mathematical Intelligencer)